2016
DOI: 10.1007/s00127-016-1263-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the people with mental illness: comparison between Czech medical doctors and general population

Abstract: Our findings demonstrate more favourable attitudes towards people with mental illness among Czech medical doctors when compared to the Czech general population. Stigma, however, is high among both these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 44 publications
(53 reference statements)
1
37
1
2
Order By: Relevance
“…Various research studies have documented stigmatising attitudes of healthcare providers and of the general population towards those with mental illness in Singapore, 3 Czech Republic 16 and Australia. 17 Compared with the general population, medical doctors in Czech Republic demonstrated more favourable attitudes towards people with mental illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research studies have documented stigmatising attitudes of healthcare providers and of the general population towards those with mental illness in Singapore, 3 Czech Republic 16 and Australia. 17 Compared with the general population, medical doctors in Czech Republic demonstrated more favourable attitudes towards people with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health professionals in Australia possess less stigmatising attitudes towards persons with mental illness than the general public. 16 17 The difference could be attributed to better knowledge of mental illness by the professionals and explained by the contact hypothesis which states that increased personal and professional contact with people with mental illness is associated with more positive attitudes and reduced stigmatisation towards them. 18–20 Other studies, however, found contradicting results where higher level of stigma was reported among healthcare providers than in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…La discriminación interfirió con la recuperación. Winkler et al, 2016 1810 miembros de la población general y 120 médicos.…”
Section: Iat; Autoinformeunclassified
“…Extensive research has been done using the CAMI scale in both European and non-European societies, particularly showing associations with sociodemographic factors such as gender, age and level of education. For example, Winkler et al [13] in their analysis of differences between medical doctors and general population in Czech Republic found that stigma was prevalent in both groups, even though medical doctors tended to have more favorable attitudes towards the mentally ill in general. Moreover, researchers in India have found high stigmatizing attitudes in rural populations, but these stances were not associated with gender or level of education, contrary to the previous findings [14] .…”
Section: Introductionmentioning
confidence: 99%